The role of ABO incompatibility in allogeneic peripheral blood stem cell transplantation - Arslan, Önder; Coşkun, Hasan Şenol; Arat, Mutlu; Soydan, Ender; Özcan, Muhit; Gürman, Günhan; Koç, Haluk (My University, 2002)
ABO incompatibility is not a contraindication for allogeneic bone marrow transplantation, but this procedure requires an extra effort for erythrocyte or plasma depletion in certain well established conditions. Some acute or delayed immunohematological complications such as acute or chronic hemolysis and pure red cell aplasia may be encountered. In this study the outcome and transplant related complications of ABO incompatible and identical cases, who have received allogeneic peripheral blood stem cells from their HLA identical siblings were compared with each other. Ninety-one patients (CML 36, AML 37, other 18) were analyzed retrospectively including 51 (60.4%) ABO identical patients and 36 (39.6%) ABO mismatched (MM) patients, who have a bi-directional MM (n= 5), major MM (n= 16), minor MM (n= 9) and Rh MM (n= 6). Median follow up was 13 (0.5-43.0) months. We did not observed any significant differences between two groups (identical vs non-identical) in terms of acute hemolysis preceding stem cell infusion, peritransplant transfusion demand, acute-and chronic graft versus host disease. There was no change in estimated disease free survival and overall survival durations. We did not observed any influence of ABO/Rh incompatibility on short term outcome in allogeneic peripheral blood stem cell transplantation in our series and did not recommend further manipulation of the infused stem cells.
Keywords: ABO incompatibility; Allo-PBSCT; Hemolysis